Simple and Inexpensive Organic Dyes with Hydrazone Moiety as π‐Conjugation Bridge for Solid‐State Dye‐Sensitized Solar Cells. Issue 3 (7th January 2013) - Urnikaite, Simona; Malinauskas, Tadas; Gaidelis, Valentas; Bruder, Ingmar; Send, Robert; Sens, Rüdiger; Getautis, Vytautas
<x xml:space="preserve">Abstract</x> Good, cheap light: A new type of D‐π‐A metal‐free organic dye for solid‐state dye‐sensitized solar cells, employing a hydrazone fragment as π‐conjugated bridge, is presented. These dyes are obtained from relatively cheap starting materials, without the use of expensive catalysts, rigorously anhydrous or oxygen‐free conditions. The whole synthesis process is simplified, and costs of the final product are reduced.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>